2014
DOI: 10.3389/fpsyg.2014.01021
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of categorization: forgetting as the basis of abstraction and generalization

Abstract: Historically, models of categorization have focused on how learners track frequencies and co-occurrence information to abstract relevant category features for generalization. The current study takes a different approach by examining how the temporal dynamics of categorization affect abstraction and generalization. In the learning phase of the experiment, all relevant category features were presented an equal number of times across category exemplars. However, the relevant features were presented on one of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…On average, participants in the Non-themed conditions learned over 16 word-object pairs (out of 24). This learning rate was comparable to a design used in Romberg & Yu [19], in which participants learned around 16 word-object pairs (out of 18) after being exposed to each pair 12 times. Moreover, participants in the Themed conditions, on average, learned over 20 word-object pairs, a rate higher than seen in many other studies.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…On average, participants in the Non-themed conditions learned over 16 word-object pairs (out of 24). This learning rate was comparable to a design used in Romberg & Yu [19], in which participants learned around 16 word-object pairs (out of 18) after being exposed to each pair 12 times. Moreover, participants in the Themed conditions, on average, learned over 20 word-object pairs, a rate higher than seen in many other studies.…”
Section: Discussionsupporting
confidence: 59%
“…This finding pointed to the possibility that semantically-themed learning contexts facilitated word learning. However, since words referring to semantically-related objects were also presented in consecutive trials in that study, it was not clear whether the blocked presentation also contributed to the observed facilitative effect, as massed presentation has been shown to enhance performance in immediate tests [19]. Another noteworthy finding of that study was that artificially induced categories (i.e., semantically-unrelated objects that co-occurred frequently) had similar, albeit weaker, facilitative effect.…”
Section: Introductionmentioning
confidence: 89%
“…In a similar vein, the work reviewed above on the use of space to bind names to objects, as well as related work (see, e.g., Richardson & Kirkham, 2004;Vlach & Kalish, 2014), highlights that understanding the role of visual memory can lead to novel insights into how children solve referential ambiguity. Critically, theories of early word learning must understand multiple senses of visual memory: how visual memory modulates attention via habituation to novelty and how visual memory is used to build representations that track which objects are where.…”
Section: Understanding How Visual and Auditory Attention Interact In mentioning
confidence: 86%
“…Third, mirror confusion could then occur because the perceived orientation information is lost in the memory code. Because this forgetting leads to non-discrimination of an image from its mirror, it appears as a generalization process, forgetting being a central mechanism of generalization (Vlach and Kalish, 2014). The credibility of this temporary forgetting is strengthened by sensitivity to mirror reversals in an earlier visual processing object-selective region, the lateral occipital sulcus, followed by tolerance to mirror reversals in one object-selective region, the posterior fusiform sulcus (Dilks et al, 2011).…”
Section: Model 1 Of Initial Mirror-equivalence and Mirror-letter Confusionmentioning
confidence: 99%